The effect of live-streaming shopping on the consumer's perceived risk and purchase intention in China - Chuling Song; Yu-li Liu (International Telecommunications Society (ITS), 2021)
Recent empirical research has indicated that the perceived risk in e-commerce affects the consumer's purchase intention. Based on the Stimulus-Organism-Response (SOR) model, this study explores the effects of environmental stimuli on the consumer's perceived risk and purchase intention within a live-streaming shopping context. Through a sample of 341 valid users, we found that 1) perceived risk has a negative effect on the consumer's purchase intention; 2) the streamer's credibility partially mediates the relationship between perceived risk and purchase intention; and 3) the interactivity is positively associated with purchase intention. These results provide possible insights into how environmental stimuli in the context of live-streaming shopping affect the consumer's perceived risk and purchase intention.
Keywords: 330; live streaming; perceived risk; purchase intention; credibility; media richness